Effect of ion bombardment on the chemical properties of crystalline tantalum pentoxide films. (July 2019) - Perez, Israel; Sosa, Víctor; Perera, Fidel Gamboa; Elizalde Galindo, José Trinidad; Enríquez-Carrejo, José L.; Mani González, Pierre Giovanni
Abstract: The effect of argon ion bombardment on the chemical properties of crystalline Ta2 O5 films grown on Si(100) substrates by radio frequency magnetron sputtering was investigated by X-ray photoelectron spectroscopy. All samples were irradiated for several time intervals [(0.5, 3, 6, 9) min] and the Ta 4 f and O 1 s core levels were measured each time. Upon analysis at the surface of the films, we observe the Ta 4 f spectrum characteristic of Ta2 O5 . Irradiated samples exhibit the formation of Ta suboxides with oxidation states Ta 1+, Ta 2+, Ta 3+ Ta 4+, and Ta 5+ . Exposing the films, after ion bombardment, to ambient for some days stimulates the amorphous phase of Ta2 O5 at the surface suggesting that the suboxides of Ta are unstable. Using a sputtering simulation we discuss that these suboxides are largely generated during ion bombardment that greatly reduces the oxygen to tantalum ratio as the irradiation time increases. The computer simulation indicates that this is due to the high sputtering yield of oxygen. Graphical abstract: Image 1 Highlights: Orthorhombic Ta2 O5 films grown by RF magnetron sputtering. Sputtering simulation of Ar bombardment on Ta2 O5 shows a high oxygen yield. XPS analysis reveals the formation of oxidation states of Ta after ion bombardment.